MODEL PENENTUAN KOMPONEN KERUGIAN NON FISIK DALAM PENGADAAN TANAH PEMBANGUNAN JALAN - Okada, Henniko; Zanuardi, Arvian (Jurnal Sosial Ekonomi Pekerjaan Umum, 2015)
Some road developments in Indonesia are hampered by the difficulty of land acquisition due to rejection from affected communities. The condition is usually caused by the compensation which excludes non pecuniary losses. This study attempts to define the components of non pecuniary losses on the land acquisition of road development as mentioned in new regulation (UU Nomor 2 Tahun 2012). Selective coding method is used to identify the losses, and modelling to develop the basis appropriate compensation based on the case studies of other land acquisition cases. The study locus are Jalan Lintas Selatan Jawa ruas Pacitan-Hadiwarno, Surabaya-Mojokerto-Kertosono highway, and Medan-Kualanamu-Bukit Tinggi highway. The result identifies 48 (forty eight) components of non pecuniary losses that is divided into 4 (four) categories : transaction and administrative costs, moving expenses, loss of location changes, and loss of assets changes. The use of non pecuniary losses component is varied to land use, both agricultural and non-agricultural. This model is expected to improve the quality of planning and its implications to accelerate the process of land acquisition in road development.